2019
DOI: 10.31590/ejosat.638608
|View full text |Cite
|
Sign up to set email alerts
|

Improving classification performance for an imbalanced educational dataset example using SMOTE

Abstract: With technology, a lot of data is formed in digital environments. One of the areas with intensive data is educational data sets. By analyzing educational data sets, students' situatiokjgjjööÖns can be predicted by foreseeing. In this way, students can be assisted by anticipating situations such as drop-out due to failure. Educational institutions can take measures to prevent such dropouts and reduce student drop-out. Thus, financial losses of students and educational institutions can be prevented. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…To develop and evaluate predictive models in identifying the likelihood of students graduating on time during their studies in university.   [11][12]    [13][14]  [15]  [16][17][18][19][20]  [21]  [22][23][24][25][26]    [27][28][29][30][31]  Table 1 illustrates the prevalence of minority classes within datasets utilized by researchers to tackle the challenge of class imbalance in identifying GOT. This imbalance arises when the dominance of the majority class eclipses the presence of minority classes, resulting in biased predictive models that yield unpredictable outcomes [12,15,16,27,28,30].…”
Section: Introductionmentioning
confidence: 99%
“…To develop and evaluate predictive models in identifying the likelihood of students graduating on time during their studies in university.   [11][12]    [13][14]  [15]  [16][17][18][19][20]  [21]  [22][23][24][25][26]    [27][28][29][30][31]  Table 1 illustrates the prevalence of minority classes within datasets utilized by researchers to tackle the challenge of class imbalance in identifying GOT. This imbalance arises when the dominance of the majority class eclipses the presence of minority classes, resulting in biased predictive models that yield unpredictable outcomes [12,15,16,27,28,30].…”
Section: Introductionmentioning
confidence: 99%
“…The most number of data in attribute the relevance educational background with graduates employment is owned by the class "not tight" namely 787 data, while there is number of the class less than 50% is "tightest" as much as 214 data, and "very tight" class as much as 304 data. The imbalanced data in each class can affect the accuracy, precision and sensitivity [10], [11]. The accuracy is the level of the success of the correct classification of all classifications for whole data regardless of the class of the data [12], so the accuracy is not enough for imbalanced data because the accuracy does not take the accuracy on each class of labels in output attribute.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic minority oversampling technique (SMOTE) is a simple method to get over the imbalanced data [10]. Several studies have shown that the SMOTE method can improve the accuracy of classifications as mentioned in studies [11], [16]- [18]. The imbalanced data is done at the pre-processing stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation